2012
DOI: 10.1103/physrevb.85.214527
|View full text |Cite
|
Sign up to set email alerts
|

Bimagnon studies in cuprates with resonant inelastic x-ray scattering at the OKedge. I. Assessment on La2CuO4and comparison with the excita

Abstract: We assess the capabilities of magnetic Resonant Inelastic X-ray Scattering (RIXS) at the O K edge in undoped cuprates by taking La2CuO4 as a benchmark case, based on a series of RIXS measurements that we present here. By combining the experimental results with basic theory we point out the fingerprints of bimagnon in the O K edge RIXS spectra. These are a dominant peak around 450 meV, the almost complete absence of dispersion both with π and σ polarization and the almost constant intensity vs. the transferred … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
69
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 43 publications
12
69
0
1
Order By: Relevance
“…This feature can be attributed to bimagnons, because (1) their energy scales are consistent with the bimagnons (160 meV for Sr 2 IrO 4 and 185 meV for Sr 3 Ir 2 O 7 ) measured by Raman scattering [47] and (2) their dispersions are in agreement with those measured by Ir L 3 RIXS [16][17][18]. Note that the bimagnons of cuprates measured by O K RIXS are nondispersive [35,36]. The presence of both single magnons and bimagnons indicates that O K RIXS is a powerful spectroscopic method for studying the magnetic dynamics of iridates.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This feature can be attributed to bimagnons, because (1) their energy scales are consistent with the bimagnons (160 meV for Sr 2 IrO 4 and 185 meV for Sr 3 Ir 2 O 7 ) measured by Raman scattering [47] and (2) their dispersions are in agreement with those measured by Ir L 3 RIXS [16][17][18]. Note that the bimagnons of cuprates measured by O K RIXS are nondispersive [35,36]. The presence of both single magnons and bimagnons indicates that O K RIXS is a powerful spectroscopic method for studying the magnetic dynamics of iridates.…”
supporting
confidence: 72%
“…Therefore, soft x-ray RIXS is a promising method for studying artificial two-dimensional samples [7,8]. However, given that SOC is absent in the O 1s level, O K RIXS is expected to be insensitive to single spin-flip excitations [31,35,36]. This would severely limit the applicability of O K RIXS on iridates and related 5d TM oxides, especially thin films and heterostructures fabricated by these materials, where magnetic excitations need to be studied for probing the low-energy Hamiltonian [15][16][17][18].…”
mentioning
confidence: 99%
“…76,78,79 Similar to our case, the two-magnon feature in the cuprates can be revealed by comparison of RIXS at the Cu L 3 edge and the O K edge. 78,79 In the optical data, a peak at 0. • (middle) and 130…”
Section: Two-orbiton Peak At the O K Edgementioning
confidence: 57%
“…It is known to be sensitive to both orbital (or d-d) excitations and to intersite charge-transfer excitations. 40,44,[75][76][77][78][79][80] To the best of our knowledge, this is the first report on the observation of Mott-Hubbard excitations in RIXS at the O K edge. The differences between the RIXS data from the O K edge and from the V L 3 edge originate from the different microscopic excitation processes.…”
Section: Two-orbiton Peak At the O K Edgementioning
confidence: 92%
“…The fast collision approximation [28][29][30] and the effective operator approach [31] suggested that only single magnon excitations or Sðq; ωÞ should be measured by RIXS at the Cu L edge [27,31,32]. More sophisticated treatments-the ultrashort core-hole lifetime (UCL) expansion [33][34][35] and the UCL-inspired ansatz [36]-highlighted that RIXS should also be sensitive to bimagnon excitations. A further extension of UCL also pointed out the importance of three-magnon excitations [37].…”
Section: When ∼10mentioning
confidence: 99%